Effect of three different nitrogen fertilizers on several vegetable crops - WIDIATI HADI ADIL; NOVIANTI SUNARLIM; IKA ROOSTIKA (Society for Indonesian Biodiversity, 2006)
Applications of three different sources of N fertilizers (urea, compost from slaughter house and chicken manure compost) on vegetable crops (tomato, okra and spinach) were conducted in the green house of Research Institute for Food Crop Biotechnology, Bogor from August of 1999 to April of 2000. Treatments consisted of: (i) without fertilizer, (ii) 5 g N/pot of urea, (iii) 10 g N/pot of slaughter house compost, (iv) 10 g N/pot of chicken manure compost, (v) 5 g N/pot of urea + 10 g N/pot of slaughter house compost, and (vi) 5 g N/pot of urea + 10 g N/pot of chicken manure compost. Completely Randomized Design with 3 replicates was used in the experiments. In the first experiment, tomatoes were planted in the first season, following by okra in the second season. In the second experiment, spinach was planted for 6 times. Urea and compost were applied only once at the beginning of the experiment. Results of the experiments showed that for the first experiment, the highest N-uptake for tomatoes and okra was obtained from the treatment 5 g N/pot of urea + 10 g N/pot of chicken manure compost, although the highest fresh weight of tomatoes and okra fruits were not from this treatment. The treatment of 10 g N/pot of either slaughter house or chicken manure composts gave the highest fresh fruits weight. In the second experiment, the highest dry weight and N-uptake of spinach were obtained from the treatment of 5 g N/pot of urea + 10 g N/pot of chicken manure compost. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: urea, compost, tomato (Lycopersicon esculentum Mill.), okra (Abelmoschus esculentus L. Moench), spinach (Amaranthus tricolor)